Analisis daya dukung lahan pertanian Indonesia pada bonus demografi tahun 2025 - Yuliani, Manis; Asrofani, Farha Widya (Social Agriculture, Food System, and Environmental Sustainability, 2024)
Currently, Indonesia is striving to achieve the Sustainable Development Goals (SDGs), one of which is to eradicate hunger. Indonesia faces significant challenges in meeting the food needs of its population. Food needs are influenced by population growth rates and the composition of the population during the demographic bonus expected to occur between 2020-2030 (Casmudi, 2016). The population of Indonesia continues to increase from year to year. Based on projection data from the Central Statistics Agency (BPS) for the period 2010-2025, Indonesia's population continues to increase at a growth rate of 1.7% per year. In 2018, the population of Indonesia was 265,015,300 (BPS, 2018). During the demographic bonus, the proportion of the working-age population is larger than that of children and the elderly. The increasing number of productive age individuals will increase the demand for rice as the staple food of the Indonesian people to fulfill nutritional needs. It is estimated that the population at the peak of the demographic bonus will be 284,829,000 (BPS, 2018) with a working-age composition of 70% (Casmudi, 2016). The increase in population and the composition of the working-age population drive the increased demand for rice. In order to support the success of the 2025 demographic bonus, adequate support is needed. The carrying capacity of agriculture, especially rice cultivation, is analyzed to determine the position of Indonesia's rice agricultural land carrying capacity so that it can be considered in formulating appropriate policies to meet food needs independently. The objective of this research is to analyze the carrying capacity of agricultural land during the demographic bonus, especially in 2025 as the peak demographic period, to determine the status of the carrying capacity of rice agricultural land. Based on the analysis of land carrying capacity in 2025 during the peak demographic bonus, the value of harvested rice land carrying capacity is 2.418, which means that Indonesia is a country that is already self-sufficient in food but has not yet been able to provide decent livelihoods for its population. Efforts that can be made to increase carrying capacity to improve the standard of living include increasing productivity and controlling the conversion of agricultural land to non-agricultural land.